Poor things : episodes from the early life of Archibald McCandless M. D. Scottish public health officer - Gray, Alasdair (HarperCollinsPublishers, 2023)
"In the 1880s in Glasgow, Scotland, medical student Archibald McCandless finds himself enchanted with the intriguing creature known as Bella Baxter. Supposedly the product of the fiendish scientist Godwin Baxter, Bella was resurrected for the sole purpose of fulfilling the whims of her benefactor. As his desire turns to obsession, Archibald's motives to free Bella are revealed to be as selfish as Godwin's, who claims her body and soul. But Bella has her own passions to pursue. Passions that take her to aristocratic casinos, low-life Alexandria, and a Parisian bordello, reaching an interrupted climax in a Scottish church. Exploring her station as a woman in the shadow of the patriarchy, Bella knows it is up to her to free herself--and to decide what meaning, if any, true love has in her life."--